Cervical Lymphadenopathy in a Nonagenarian Woman: What to Think? - Vanessa Meireles Chaves; Fernando Nogueira; Gilberto Pires da Rosa; Sofia Tavares; Inês Ferreira; Ana Oliveira Monteiro; Ester Ferreira (European Journal of Case Reports in Internal Medicine, 2019)
Tuberculosis remains a worldwide public health problem. Cervical tuberculous lymphadenitis (TBL) or scrofula is the most common form of extrapulmonary tuberculosis, affecting the cervical lymph nodes. We report the case of a 93-year-old woman presenting with cervical adenopathies with 3 months duration. Fine needle aspiration (FNA) biopsy yielded a noncaseous granulomatous process, but was negative for Mycobacterium tuberculosis (MT). As the adenopathies had grown, an excisional biopsy was performed. An extensive study of infectious aetiologies was performed, including for MT, with a negative outcome. Owing to the persistence of cervical lymphadenitis with caseous granulomas, a diagnosis of TBL was strongly suspected and presumptive treatment was initiated. Afterwards, diagnostic confirmation was obtained by isolation of MT in the lymph node culture. The patient presented a favourable clinical outcome. This case highlights that a high index of suspicion is essential for the diagnosis of TBL, especially in the elderly, and emphasizes the importance of pursuing diagnostic confirmation, in which FNA and excisional biopsy plays a key role.